Derivation and Clinical Validation of a Redox-Driven Prognostic Signature for Colorectal Cancer - Dang, Qin; Liu, Zaoqu; Hu, Shengyun; Chen, Zhuang; Meng, Lingfang; Hu, Junhong; Wang, Guixian; Yuan, Weitang; Han, Xinwei; Li, Lifeng; Sun, Zhenqiang (Frontiers in Oncology, 2021)
Colorectal cancer (CRC), a seriously threat that endangers public health, has a striking tendency to relapse and metastasize. Redox-related signaling pathways have recently been extensively studied in cancers. However, the study and potential role of redox in CRC remain unelucidated. We developed and validated a risk model for prognosis and recurrence prediction in CRC patients via identifying gene signatures driven by redox-related signaling pathways. The redox-driven prognostic signature (RDPS) was demonstrated to be an independent risk factor for patient survival (including OS and RFS) in four public cohorts and one clinical in house cohort. Additionally, there was an intimate association between the risk score and tumor immune infiltration, with higher risk score accompanied with less immune cell infiltration. In this study, we used redox-related factors as an entry point, which may provide a broader perspective for prognosis prediction in CRC and have the potential to provide more promising evidence for immunotherapy.